Implementation of Expert System to Diagnose Pregnancy Disorders using Fuzzy Expert System Method (Universitas Negeri Semarang, 2021)
The process of problem analysis can be carried out by a computer system that has included a knowledge base and a set of rules from an expert, known as an expert system. One of the problems that the expert system can solve is to diagnose pregnancy disorders. This study aims to determine how to design an expert system by adopting a doctor's expertise with the fuzzy expert system method. The data used in this study were 46 data obtained from the medical records from Tugurejo Hospital in Semarang City. The variables used were general symptoms and pregnancy disorders. The result of this research is the implementation of the fuzzy expert system to diagnose pregnancy disorders. The level of system accuracy generated from the scenario of 26 data as training data and 20 data as test data is equal to 95%.